Ferrocenyl Ionic Compounds Based on 5‐Ferrocenyl‐1H‐tetrazole. Synthesis, Characterization, Migration, and Catalytic Effects During Combustion1. Issue 2 (4th December 2015) - Gao, Xiaoni; An, Ting; Li, Jizhen; Zhao, Fengqi; Fan, Xuezhong; Li, Xinyan; Zhang, Guofang; Gao, Ziwei
Abstract: Ferrocenyl ionic compounds, consisting of the 5‐ferrocenyltetrazolate anion and a guanidinium or a 1‐alkyl‐3‐methylimidazolium cation, were synthesized and characterized by 1 H NMR, 13 C NMR, and UV/Vis spectroscopy, as well as elementary analysis. The molecular structures of four compounds were additionally confirmed by single‐crystal X‐ray diffraction. Results of the TG and DSC analyses showed that some compounds display high thermal stability. Cyclic voltammetry investigations suggested that the compounds exhibit redox waves for the ferrocenyl groups and are considered as irreversible redox systems. Migration studies revealed that migration trends of the compounds are much lower than that of 2, 2‐bis(ethylferrocenyl)propane (Catocene), extensively used in composite solid propellants. Their catalytic performances for thermal decomposition of ammonium perchlorate (AP), 1, 3, 5‐trinitro‐1, 3, 5‐triazacyclohexane (RDX), and 1, 2, 5, 7‐tetranitro‐1, 3, 5, 7‐tetraazacyclooctane (HMX) were evaluated by DSC and/or TG techniques. Most of the compounds exhibit high catalytic efficiency in the thermal degradation of AP and RDX. Those of the guanidine‐containing compounds1 –3 are better, implying that nitrogen‐rich moieties are beneficial to enhancing released heats of some energetic materials. These guanidine salts could be used as ferrocene‐based burning rate catalyst candidates in composite solid propellants. Abstract :